KEDUDUKAN PEREMPUAN DALAM KAJIAN KESETARAAN GENDER PERSPEKTIF HUKUM ISLAM - Lumita Wulandari Hasibuan; Darania Anisa (Ahwaluna | Jurnal Hukum Keluarga Islam, 2026)
There is a negative stigma which assumes that Islam does not respect the position of women, limits its freedom is unjust and makes women a second-class human being under the control of men. These reasons make this writing is interested.Departing from that thought, they also considered that Islam wash the main obstacle to the strunggle for gender aquality.The purpose of this study is to uncover the core problem of gender aquality in an islamic perspective.This research wash conducted using islami study methods and approaches.The position of woman in islam has the same rights and obligation as men, althought there are somethings that woman cannot do and men can do, and vice versa.As for what distinguishes the degree between men and women is the level of piety.Islam has far raised the status of women and it can be said that in other religions there is nothing like and even exceeding the privileges of women other than in Islam.